2014
DOI: 10.17795/mejrh-24268
|View full text |Cite
|
Sign up to set email alerts
|

The Criteria of Choosing a Right Partner From the Point of View of Unmarried Students of Semnan University of Medical Sciences

Abstract: Background: Regarding the process of increasing the divorce rate in recent years and youth population, the awareness among the youth, especially the university students, about marriage and criteria of choosing a right partner for proper planning to preserve family is of great importance. Objectives: The aim of this study was to investigate the viewpoint of unmarried students of Semnan University of Medical Sciences about the criteria of choosing the right partner. Materials and Methods: This cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The first part of the questionnaire included the participant's basic demographic questions, including age, sex, place of residence, educational level, number of children per family, number of births, father's education and occupation, mother's education and occupation, parent's monthly income, and their views on cohabitation (Table 1). The second part of the questionnaire included 46 items of spouses' basic selection criteria, based on the Likert scale (Table 2), from "very low important (1), partially important (2), desirable (3), important (4), and essential" (5). The questionnaire items included psychological domain 39% (18/46), economic domain 11% (5/46), social domain 9% (4/46), familial domain 7% (3/46), cultural domain 22% (10/46), and physical domain 11% (5/46) (Table 2).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first part of the questionnaire included the participant's basic demographic questions, including age, sex, place of residence, educational level, number of children per family, number of births, father's education and occupation, mother's education and occupation, parent's monthly income, and their views on cohabitation (Table 1). The second part of the questionnaire included 46 items of spouses' basic selection criteria, based on the Likert scale (Table 2), from "very low important (1), partially important (2), desirable (3), important (4), and essential" (5). The questionnaire items included psychological domain 39% (18/46), economic domain 11% (5/46), social domain 9% (4/46), familial domain 7% (3/46), cultural domain 22% (10/46), and physical domain 11% (5/46) (Table 2).…”
Section: Data Collectionmentioning
confidence: 99%
“…The first category is the primary criteria (characteristics, ethics, and individual beliefs) that are more stable, and the second category is the secondary criteria (appearance, economic status, and well-being) that are less tolerable and resilient. 4,5 In comparison to Western societies, Iranian families play an important role in spouse selection and it is concluded that Iranian families consider selection as the parent's right for their children. There is a premise that individuals bring factors from their families into marriage life that may affect their relationship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation